2011
DOI: 10.1136/neurintsurg-2011-010083
|View full text |Cite
|
Sign up to set email alerts
|

Covered stents safely utilized to prevent catastrophic hemorrhage in patients with advanced head and neck malignancy

Abstract: The use of covered stents for avoidance of catastrophic hemorrhage following treatment in patients with head and neck tumors with bilaterally threatened carotid arteries was successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 15 publications
2
40
0
Order By: Relevance
“…This outcome's low complication rate is comparable with those reported in the literature (Table II) [6][7][8][9][10][11] and highlights the efficacy of using self-expandable stent grafts in emergency practice to achieve hemostasis and prevent the high neurologic morbidity (20%) associated with carotid occlusion. This outcome's low complication rate is comparable with those reported in the literature (Table II) [6][7][8][9][10][11] and highlights the efficacy of using self-expandable stent grafts in emergency practice to achieve hemostasis and prevent the high neurologic morbidity (20%) associated with carotid occlusion.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This outcome's low complication rate is comparable with those reported in the literature (Table II) [6][7][8][9][10][11] and highlights the efficacy of using self-expandable stent grafts in emergency practice to achieve hemostasis and prevent the high neurologic morbidity (20%) associated with carotid occlusion. This outcome's low complication rate is comparable with those reported in the literature (Table II) [6][7][8][9][10][11] and highlights the efficacy of using self-expandable stent grafts in emergency practice to achieve hemostasis and prevent the high neurologic morbidity (20%) associated with carotid occlusion.…”
Section: Discussionsupporting
confidence: 79%
“…Although graft infection was commonly reported in the literature, 6,10,14,15 none occurred in our study despite a wound infection being present in three patients. This low rate (15%), compared to the Chang et al's series (40%), 10 7 where patients received optimal antithrombotic treatment (heparin and a bolus of aspirin and clopidogrel before stent implantation) and were maintained on lifelong dual antiplatelet medications; however, 80% of his their patients presented with post-treatment bleeding. We encountered three stent occlusions in our series with a mean of 2 months; all patients received heparin at the time of stent delivery and aspirin starting the day of stent implantation.…”
Section: Discussionmentioning
confidence: 76%
“…The MINORS quality scores ranged from 7 to 11. An overview of the characteristics of the studies is provided in Table …”
Section: Resultsmentioning
confidence: 99%
“…An overview of the characteristics of the studies is provided in Table 1. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Of the 292 patients, 26 patients did not have relevant or extractable data. Of the remaining 266 patients, 137 were treated with embolization (77 for ICA and/or CCA and 60 for ECA).…”
Section: Literature Reviewmentioning
confidence: 99%
“… 77 Other authors have also observed significantly lower rebleeding rates with embolization (11%–21%) compared with covered stents (25%–85%) ( Table 3 ). 1 , 22 , 28 , 69 , 70 , 73 , 78 86 Short- and long-term rebleeding after stent placement can occur from the stented carotid artery as a result of either persistent endoluminal leakage or involvement of the carotid artery with tumor either proximal or distal to the stent, as well as due to erosion of the arterial wall by the stent. Existence of an uncontrolled ongoing infection at the stent site is an important factor associated with recurrent CBS.…”
Section: Cbs After Reirradiation Of a Recurrent Tumormentioning
confidence: 99%